Weimar Surfaces : Urban Visual Culture in 1920s Germany - Ward, Janet, 1963- (Book collections on Project MUSE., 2001)
This study revisits Weimar Germany via the lens of metropolitan visual culture, analyzing the power that 1920s Germany holds for today's visual codes of consumerism.